"المفاضلة بين نماذج garch للتنبؤ بعوائد تقلبات أسعار النفط - دراسة قياسية: النفط في الدول العربية خلال الفترة 2002/2022 " - عبد الجبار, التجاني; فيصل, صوالح احميمه; محمد البشير, تجاني (University of eloued جامعة الوادي, 2021)
"في دراستنا هذه المتعلقة بالمفاضلة بين نماذج garch للتنبؤ بعوائد تقلبات أسعار النفط، حيث تطرقنا للفصل التطبيقي إلى واقع اسعار النفط في الدول العربية في المبحث الأول الخاص بعرض أهم المؤشرات المالية أسعار النفط يتضح لنا هشاشة تلك المؤشرات وعدم استقراريتها، حيث سجل في مجملها فترات تراجع حادة سواء. وفي المبحث الثاني تم تحديد مختلف مراحل المنهجية القياسية، حيث بينا من خلاله كيفية دراسة استقرارية سلاسل العوائد المتعلقة بمتغيرات الدراسة، وأهم الاختبارات القياسية التي تحدد مدى السكون، في حين تم كذلك كيفية دراسة اختبار التوزيع الطبيعي و معامل الالتواء والتفلطح، ناهيك عن فحص لخاصيتي الارتباط الذاتي وعدم ثبات التباين، وكما بينا ي حالة عدم توفر تلك الخاصيتين ضرورة الاعتماد على نموذج أنجل قرانجر في تقدير العلاقة بين متغيرات الدراسة وفي المبحث الثالث التطبيقي تم التطرق لعرض نتائج الدراسة القياسية والتي تم الكشف في أولى مراحلها على مدى استقرارية عوائدها في حين تم تقدير معادلة العائد على الثابت وفحص مشكل الارتباط الذاتي وعدم ثبات التباين، والتي تبين أنه يوجد ارتباط ذاتي بين بين الفترة الحالة والفترات السابقة. وعند تطبيقنا لنموج الارتباط الذاتي المشروط بعدم تجانس الأخطاء يتبين لنا اختفاء خاصية ثبات التباين والارتباط الذاتي، في حين دلت نتائجنا كمرحلة ثانية عدم وجود تكامل مشترك. ""The study aimed to identify the laws that organized electronic media in Algeria and try to establish a knowledge base about electronic media legislation in Algeria, and to show the difference between electronic media and traditional media, and the research problem was the extent of the effectiveness of legal materials in regulating the practice of electronic media in Algeria, and after determining The problem Several questions were asked, the most important of which are: How did the Algerian general media law regulate the practice of electronic media? Did the Algerian legislator come up with anything new in the field of regulating the practice of electronic media? Is there a difference between the recent media laws in the field of electronic media regulation? The study relied on the analytical approach to analyze the Executive Decree 20-332 of the Media Law 2020, and relied on the use of one of the research tools, which is observation, and the research sample is the legal materials that dealt with electronic media in Algeria. In the end, the study reached a number of results, the most important of which are: • The legislator stipulated for the practice of media activity via the Internet that the practitioner be a natural person of Algerian nationality or a legal person subject to Algerian law, and that the capital be owned by persons who enjoy Algerian nationality. • The legislator requires that media activity be subject to the Internet via a website. • This site or the media organization is run by a manager responsible for the online media apparatus, and the law stipulates a set of conditions and the director is bound by a set of obligations. "
ماستر تجارة
Keywords: المفاضلة، garch، اسعار النفط.; Trade-off, garch, oil prices